2017
DOI: 10.1080/14756366.2017.1302440
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen therapy modulates serum OPG/RANKL in femoral head necrosis patients

Abstract: Hyperbaric oxygen therapy (HBOT) has beneficial effects on avascular necrosis of femoral head (ANFH), but its mechanism of action is still unclear. We investigated if HBOT upregulates serum osteoprotegerin (OPG) and/or inhibits osteoclast activation. 23 patients with unilateral ANFH at stage I, II and III consented to the study: the patients received standard HBOT. Serum OPG levels were obtained at the beginning of HBOT (T0), after 15 sessions (T1), 30 sessions (T2), after a 30-day break (T3), and after 60 ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 31 publications
(27 reference statements)
1
29
0
1
Order By: Relevance
“…Current treatments are typically invasive and, depending on the bone-affecting disease, they involve grafting, surgery, debridement, and/or pharmacotherapy [2]. Recently, hyperbaric oxygen (HBO) has been proposed as an adjunctive therapy in the management of several conditions requiring bone healing [3][4][5][6]. The HBO therapy is the noninvasive administration of 100% O 2 at pressures greater than one atmosphere absolute (ATA).…”
Section: Introductionmentioning
confidence: 99%
“…Current treatments are typically invasive and, depending on the bone-affecting disease, they involve grafting, surgery, debridement, and/or pharmacotherapy [2]. Recently, hyperbaric oxygen (HBO) has been proposed as an adjunctive therapy in the management of several conditions requiring bone healing [3][4][5][6]. The HBO therapy is the noninvasive administration of 100% O 2 at pressures greater than one atmosphere absolute (ATA).…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Numerous in vitro and in vivo studies also strongly suggested that GCs were able to inhibit the growth and differentiation of bone cells, thus affecting the reconstruction and resorption of bones and decreasing the bone conversion rate, which further leads to bone destruction, and the deposit of apoptotic bone cells. 6,7 Numerous in vitro and in vivo studies also strongly suggested that GCs were able to inhibit the growth and differentiation of bone cells, thus affecting the reconstruction and resorption of bones and decreasing the bone conversion rate, which further leads to bone destruction, and the deposit of apoptotic bone cells.…”
mentioning
confidence: 99%
“…role in the initiation and pathogenesis of femoral head necrosis. 6,7 Numerous in vitro and in vivo studies also strongly suggested that GCs were able to inhibit the growth and differentiation of bone cells, thus affecting the reconstruction and resorption of bones and decreasing the bone conversion rate, which further leads to bone destruction, and the deposit of apoptotic bone cells. 8 Therefore, it is critical to understand the pathological mechanisms underpinning this condition and to develop proper therapeutics to disrupt the progression of SANFH.…”
mentioning
confidence: 99%
“…OPG, the soluble decoy receptor for RANKL, inhibits RANKL binding to receptor activator of NF-kB (RANK) and prevents osteoclastogenesis and bone resorption. [32][33][34] RANK-RANKL/OPG ratios and the level of other inflammatory cytokines, such as TNF, constitute critical mediators of osteoclastogenesis in diabetes with periodontal disease. 11,35,36 The RANKL/OPG ratio has been reported to increase in periodontal diseases such as periodontitis.…”
Section: Discussionmentioning
confidence: 99%